2007
DOI: 10.1007/s10530-007-9118-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Conchophthirus acuminatus (Protista: Ciliophora) in Dreissena polymorpha (Mollusca: Bivalvia) along the River Shannon, Ireland

Abstract: Samples of Dreissena polymorpha were collected at several sites along the River Shannon navigation in Ireland, to determine the occurrence and distribution of their obligate host-specific commensalistic ciliate, Conchophthirus acuminatus, in this newly invaded region. Mussels collected by various methods were fixed immediately in 75% ethanol, in which they were later dissected under a stereoscopic microscope, beginning with thorough flushing of the mantle cavity and removal of the gills. One ml of sediment flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They probably feed on epithelial cells shed by their host. Conchophthirus species are widely distributed and have been detected in many countries in Asia (Deshmukh et al 2011 ; Kahl 1931 ; Uyemura 1935 ), Europe (Burlakova et al 1998 , 2006 ; Chuševė et al 2012 ; Conn et al 2008 ; Dobrzańska 1958 ; Fenchel 1965 , 1966 ; Fokin et al 2003 ; Karatayev and Burlakova 2022 ; Karatayev et al 2000a , b , 2007 ; Laruelle et al 1999 ; Mastitsky 2012 ; Mastitsky et al 2008 ; Mermod 1914 ; Molloy et al 2010 ; Raabe 1933 , 1934 , 1950 , 1966 , 1971 ; Zhang and Vďačný 2024 ) and North America (Antipa and Hatzidimitriou 1981 ; Antipa and Small 1971a , b ; Antipa et al 2020 ; Kidder 1934 ; Laruelle et al 2002 ; Penn 1958 ). In addition, Conchophthirus species inhabit a diverse array of freshwater bivalve groups.…”
Section: Discussionmentioning
confidence: 99%
“…They probably feed on epithelial cells shed by their host. Conchophthirus species are widely distributed and have been detected in many countries in Asia (Deshmukh et al 2011 ; Kahl 1931 ; Uyemura 1935 ), Europe (Burlakova et al 1998 , 2006 ; Chuševė et al 2012 ; Conn et al 2008 ; Dobrzańska 1958 ; Fenchel 1965 , 1966 ; Fokin et al 2003 ; Karatayev and Burlakova 2022 ; Karatayev et al 2000a , b , 2007 ; Laruelle et al 1999 ; Mastitsky 2012 ; Mastitsky et al 2008 ; Mermod 1914 ; Molloy et al 2010 ; Raabe 1933 , 1934 , 1950 , 1966 , 1971 ; Zhang and Vďačný 2024 ) and North America (Antipa and Hatzidimitriou 1981 ; Antipa and Small 1971a , b ; Antipa et al 2020 ; Kidder 1934 ; Laruelle et al 2002 ; Penn 1958 ). In addition, Conchophthirus species inhabit a diverse array of freshwater bivalve groups.…”
Section: Discussionmentioning
confidence: 99%
“…Parasites, commensals, and other symbionts of dreissenids are currently being actively studied (Mastitsky 2004;Stunžėnas et al 2004;Burlakova et al 2006;Conn et al 2008;Molloy et al 2010;Petkevičiūtė et al 2015;Travina et al 2019Travina et al , 2021. Among parasites and commensals associated with zebra mussels, at least seven genera of trematodes are known: Bucephalus Baer, 1827 (Digenea: Bucephalidae), Phyllodistomum Braun, 1899 (Digenea: Gorgoderidae), Echinoparyphium Dietz, 1909and Echinostoma Rudolphi, 1809(Digenea: Echinostomatidae), Sanguinicola Plehn, 1905, Leucochloridiomorpha Carus, 1835 (Digenea: Brachylaemidae), metacercariae belonging to the Plagiorchiidae Lühe, 1901 (Digenea), and Aspidogaster von Baer, 1826 (Aspidogastrea: Aspidogastridae).…”
Section: Discussionmentioning
confidence: 99%
“…The two species were not mixed at any point once being removed from the river. Exploratory dissection on both ethanolstored and live mussels showed that the storage of mussels in ethanol prior to analysis did not affect the detection of any parasites in the study, and it has previously been shown as an effective way of sampling mussel parasites (Conn et al, 2008). As we only sampled non-threatened non-cephalised invertebrates, no ethical approval was required.…”
Section: Sampling Regimementioning
confidence: 99%